ACROMEGALIC CARDIOMYOPATHY IN AN OLDER ADULT: A CASE REPORT AND A REVIEW OF DIAGNOSTIC AND THERAPEUTIC APPROACHES - Tran Vo Tri, Dung; Hoàng Lưu, Tạ; Quốc Phòng, Nguyễn; Thị Kim Ngọc, Nguyễn; Trung Kiên, Trần; Thanh Vy, Nguyễn; Thị Mai Hương, Nguyễn; Thanh Huân, Nguyễn (Journal of Health and Aging, 2026)
Acromegalic cardiomyopathy is classified as an endocrine cardiomyopathy. Acromegaly is characterized by the hypersecretion of Growth Hormone (GH) and its peripheral mediator, Insulin-like Growth Factor 1 (IGF-1). The etiology in the majority of cases is a pituitary adenoma. Chronic elevation of circulating GH and IGF-1 levels affects cardiomyocyte growth, myocardial contractility, and triggers various indirect mechanisms culminating in cardiomyopathy. The clinical phenotype typically presents as hypertrophic cardiomyopathy; however, without hormonal control, it may progress to a dilated cardiomyopathy phenotype with reduced ejection fraction. In this article, we report a clinical case in an older patient presenting with dyspnea. Based on clinical and diagnostic findings, the patient was diagnosed with acromegaly secondary to a pituitary adenoma, complicated by heart failure with reduced ejection fraction (HFrEF). Management included diuretics for decongestion and optimization of Guideline-Directed Medical Therapy (GDMT), with planned pituitary tumor resection upon stabilization of heart failure. However, the patient declined surgical intervention.
Keywords: cardiomyopathy; acromegaly; acromegalic cardiomyopathy